Design criteria for minimalist mimics of protein–protein interface segments. Issue 4 (10th January 2019) - Taechalertpaisarn, Jaru; Lyu, Rui-Liang; Arancillo, Maritess; Lin, Chen-Ming; Jiang, Zhengyang; Perez, Lisa M.; Ioerger, Thomas R.; Burgess, Kevin
Abstract : We present several critical design criteria of minimalist peptidomimetics deduced via extensive computational and data-mining studies on nine representative mimic designs. Abstract : Small molecules that can interrupt or inhibit protein–protein interactions (PPIs) are valuable as probes in chemical biology and medicinal chemistry, but they are also notoriously difficult to develop. Design of non-peptidic small molecules that mimic amino acid side-chain interactions in PPIs ("minimalist mimics") is seen as a way to fast track discovery of PPI inhibitors. However, there has been little comment on general design criteria for minimalist mimics, even though such guidelines could steer construction of libraries to screen against multiple PPI targets. We hypothesized insight into general design criteria for minimalist mimics could be gained by comparing preferred conformations of typical minimalist mimic designs against side-chain orientations on a huge number of PPI interfaces. That thought led to this work which features nine minimalist mimic designs: one from the literature, and eight new "hypothetical" ones conceived by us. Simulated preferred conformers of these were systematically aligned with >240 000 PPI interfaces from the Protein Data Bank. Conclusions from those analyses did indeed reveal various design considerations that are discussed here. Surprisingly, this study also showed one of the minimalist mimic designs aligned on PPI interface segments more than 15 times more frequently than any other in the series (according to uniform standards described herein); reasons for this are also discussed.